The plurilingual classroom and ELT: The challenge to overcome tensions between aboriginal languages and hegemonic languages - Helver, Adriana María (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This pedagogic proposal describes a CLIL (Content and Language Integrated Learning) project for the secondary school English language classroom that integrates English, art and citizenship education with the aim to promote a hetereglossic view of language practices in multicultural ELT classrooms and the development of intercultural competences in the framework of linguistic rights. The project is intended to be developed in twelve lessons with 15-16 year-olds. Students will read and research, through the use of different multimodal material, about the importance of preserving local aboriginal languages; they will also develop cooperative works (murals, bilingual version of English songs, timelines) that relate and integrate local languages with English.